Danos ocasionados por dichelops melacanthus (heteroptera:pentatomidae) em hÍbridos convencionais e transgÊnicos de milho - Crosariol Netto, Jacob [UNESP]; Michelotto, Marcos Doniseti; Grigolli, José Fernando Jurca; Galli, Juliana Altafin; Pirotta, Melina Zacarelli [UNESP]; Busoli, Antonio Carlos [UNESP] (My University, 2015)
This study evaluated the symptoms of attack by the green belly stink bug, Dichelops melacanthus (Dallas, 1851), in conventional and transgenic commercial corn (Zea mays) hybrids, the seeds of which were either treated using the insecticide thiamethoxam or without chemical treatment. The experiment was conducted during the 2010/2011 crop season in Pindorama, São Paulo State, Brazil. The percentage of plants with symptoms or injuries was recorded by visually evaluating the degree or intensity of attack symptoms. The height of the plants was also recorded on a weekly basis, until the plants were 40 DAE. We also measured yield compounds, such as the number of rows of grain/spikes, spike weight (with and without straw), and grain weight. The seeds of hybrids that had previously been treated with thiamethoxam showed lower percentage of the number of plants that were attacked. Further, the grain weight of the plants increased 29.5% more than that of plants from untreated seeds. It was also found that transgenic hybrids exhibited lower height reduction in 40 DAE plants than did conventional isolines. Visual inspection is effective in assessing the degree of injury caused by attacks to the developing plants.
Damages caused by dichelops melacanthus (Heteroptera: Pentatomidae) in conventional and transgenic corn hybrids
Keywords: Insect; Seed treatment; Transgenesis; Yield; Zea mays